Владимир Высоцкий знакомый и незнакомый - Георгиев Любен (Искусство, 1989)
Экземпляры: ЧЗ (20151223) / Инвентарный номер: 26148 / Цена: 1.20 / Сис.шифр: 83.3(2=Рус)7-8Высоцкий / Авт.знак: Г36 / ГРНТИ: 17.09 / ББК: 83.3(2=Рус)7-8Высоцкий